Clarice Lispector entre cartas : sua correspondência com Lúcio Cardoso, Fernando Sabino e outros - Mariana Magalhães Miranda (2019)
This paper aims to analyze and problematize the letters of Clarice Lispector and their correspondents such as Lúcio Cardoso, Fernando Sabino and their sisters in the book “Minhas Queridas” in order to understand and approximate the author's creative process, writing and style of epistolary theory. Readings by Roland Barthes, Rainer Maria Rilke, Virginia Woolf, Jacques Lacan, Sigmund Freud and Hélène Cixous will be worked to research and to analyze of an approximation of the creative process of Clarice Lispector. Regarding the relationship between life and writing, the biographical clippings studied and elaborated by Nádia Gotlib and Benjamin Moser will also be worked on in order to bring Clarice Lispector's letters and her creative process of the writing into each context and time of her life.